A simulation tool for downlink long term evolution-advanced - Mohd. Ramli, Huda Adibah; Sandrasegaran, Kumbesan; Ismail, Ahmad Fadzil; Abdul Latif, Suhaimi; Mohd. Isa, Farah Nadia (Maxwell Scientific Organization, 2014)
Long Term Evolution-Advanced (LTE-A) is an emerging mobile cellular system envisaged to provide better quality of multimedia applications. Packet scheduling becomes paramount as the LTE-A delivers multimedia applications using packet switching technology. Given that LTE-A is a new technology, its ability to satisfy the Quality of Service (QoS) requirements of multimedia applications demands further performance study. At present, a number of LTE-A simulators are available. However, these simulators in general are too specific in nature or their source codes are not publicly accessible for the research communities. As such, this paper presents a novel simulation tool to assist the research communities to study the downlink LTE-A and further optimize packet scheduling performance. This simulation tool accurately models the downlink LTE-A taking user mobility, carrier aggregation, packet scheduling and other aspects that are relevant to the research communities into consideration. The efficacy of the simulation tool is validated through performance study of a number of well-known packet scheduling algorithms.